2014
DOI: 10.1063/1.4871187
|View full text |Cite
|
Sign up to set email alerts
|

High-k dielectrics on (100) and (110) n-InAs: Physical and electrical characterizations

Abstract: Two high-k dielectric materials (Al2O3 and HfO2) were deposited on n-type (100) and (110) InAs surface orientations to investigate physical properties of the oxide/semiconductor interfaces and the interface trap density (Dit). X-ray photoelectron spectroscopy analyses (XPS) for native oxides of (100) and (110) as-grown n-InAs epi wafers show an increase in As-oxide on the (100) surface and an increase in InOx on the (110) surface. In addition, XPS analyses of high-k (Al2O3 and HfO2) on n-InAs epi show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…The obtained estimate of about 1 nm would agree with the width of the As distribution at the interface of InAs with an a-Al 2 O 3 layer grown under similar conditions as reported in Ref. 15 (cf. Fig.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The obtained estimate of about 1 nm would agree with the width of the As distribution at the interface of InAs with an a-Al 2 O 3 layer grown under similar conditions as reported in Ref. 15 (cf. Fig.…”
Section: Resultssupporting
confidence: 79%
“…7 Similarly, the InAs/Al 2 O 3 stack can be used to improve the electrical quality of GaSb p-type channels. [8][9][10] Most importantly, InAs is considered as a high mobility electron channel in a variety of transistor configurations ranging from planar metal-oxidesemiconductor (MOS) field-effect transistors (FETs) [11][12][13] to nano-wire FETs 14,15 and band-to-band tunneling devices. 16,17 The major difficulty in the realization of practically useful InAs-based transistors appears to be the poor electrical quality of interfaces with deposited oxide insulators.…”
Section: Introductionmentioning
confidence: 99%
“…A Gaussian D it distribution with peak at 1.4 × 10 13 cm −2 eV −1 centered at the InAs conduction band edge ( E c ) and at the high-k/InAs interface was included to account for defects in the device. This D it distribution is similar to experimentally obtained values for InAs with similar surface treatment prior to high-k deposition and high-k 19 . Other defects, such as traps at GaSb-InAs, GaSb-GaAs, or GaAs-InAs interface were not included as none were observed in TEM.…”
Section: Resultssupporting
confidence: 89%
“…As Si-based complementary metal oxide semiconductor (MOS) devices are being aggressively scaled down in the semiconductor industry, more elaborate gate stacks with sub-1 nm equivalent oxide thickness (EOT) gate dielectrics and high mobility channel materials with a low power consumption are required for use in MOS device applications. In the next generation large scale integrations, Hf-based gate dielectrics (high-κ) on III–V compound semiconductors such as GaAs, InGaAs, and InAs are being seriously considered. Among them, HfO 2 /InAs (bulk mobility ∼30 000 cm 2 V –1 s –1 ) shows high band offsets of over 2.0 eV, a high transconductance, high drive current at low voltages, and high-frequency operation, which are all very promising electrical properties for use in MOS devices. However, it was reported that the electrical properties of HfO 2 /InAs are significantly affected by the crystalline structure of the high-κ dielectric layer and the surface orientation of the InAs substrate. In addition, calculated electronic structure of the HfO 2 /InAs interface using density functional theory showed that interfacial defect states within InAs band gap are inevitably generated. , In particular, the elemental As states at the HfO 2 /InAs interface leads to the development of a large amount of midgap traps and oxide charge traps. Therefore, it is essential to develop a systematic understanding of the origin of the interfacial defect states in HfO 2 /InAs and to develop various defect control technique for further development.…”
Section: Introductionmentioning
confidence: 99%